Znaczenie metabolizmu tlenowego siatkówki w patogenezie zwyrodnienia plamki związanego z wiekiem - Nowak, Michał; Gnitecki, Witold; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Age-related macular degeneration (AMD) is the leading cause of visual loss in individuals over 60 years old, in developed countries. This article provides the latest information about the role of retinal oxygen metabolism in origin of that disease. It is considered that reactive oxygen species (ROS), including free radicals are responsible for apoptotic cell death and developing of pathological changes in AMD. Exposure to visible light induces dysfunction of retinal pigment epithelial cells, accumulation of lipoprotein aggregates in Bruch’s membrane, formation of drusen, and final results are damage to photosensitive retina, which leads to AMD. There are many of antioxidant systems in retina, which protect tissue from ROS. In this review we focus on their actions in terms of mechanisms of preventing oxidative damage and their potential role in therapy of AMD. There is strong evidence suggesting the supporting role of the nutritional antioxidant supplementation and protection from exposure to the visible light in the prevention and treatment of age-related macular degeneration.